(untitled) (Global Journal of Human-Social Science, 2012)
An actor must work all his life cultivate his mind train his talents systematically develop his character he may never despair and never relinquish this main purpose to love his art with all his strength and love it unselfishly Constantin Stanislavski You follow the same law of improvisation which is that you do whatever your impulse as the character- tells you to do but in this case you re the character so you have no imaginary situation to hide behind and you have no other person to hide behind What you re doing in fact is asking those questions Stanislavski said that the actor should constantly ask himself as a character Who am I Why am I here Where do I come from but instead of applying them to a role you apply them to yourself Excerpt from the Script My Dinner with Andr Wallace Shawn and Andr Gregory